"Acquiring the Skills Needed to Communicate What Is in Our Teams' Heart: Love, Compassion and Partnership": Qualitative Analysis of Intact Multidisciplinary Teams' Experience of Relationship-Centered Communication Training. (June 2022) - Middour-Oxler, Brandi; Hirschmann, Krista; Chace, Carol; Collins, Lauren; Gordon, Chandra; Mann, Michelle; Swope, Chandler; George, Cynthia
The Partnership Enhancement Program (PEP) is a 6-hour relationship-centered communication training for intact cystic fibrosis (CF) teams. The aim of this study was to analyze qualitative responses from survey participants regarding their takeaways from the training. A total of 210 professionals participated in 20 pilot workshops at 19 care centers in the United States from November 2018 to December 2019. After the workshop, qualitative feedback was captured by PEP facilitators during a feedback gathering session or submitted immediately in writing by participants. The manuscript team used grounded theory and qualitative methods of coding to identify recurring themes across participant responses. Thematic analysis revealed 5 primary themes and a web of interconnected subthemes. Primary themes include the acquisition of skills to improve communication, strengthened patient/provider connection, improved quality of communication, improved team building, and the ability to change and enhance practice. Participants who completed PEP training endorse acquiring communication skills that increase coproduction of care with patients and caregivers as well as improve relationships across the healthcare system.